Ressurrection of Curimatus albula Lütken (Characiformes: Curimatidae), a senior synonym of Cyphocharax lundi Dutra, Penido, Mello & Pessali - Dutra, Guilherme Moreira; Penido, Iago De Souza; Pessali, Tiago Casarim; Netto-Ferreira, Andre Luiz (Zootaxa, 2017)
Curimatus albula Lütken 1874 was described from the Ribeirão da Mata at Lagoa Santa, a tributary of Rio das Velhas, Rio São Francisco basin. The species validity was questioned by Lütken (1875) himself, who suggested that the species could be a synonym of Curimatus gilbert Quoy & Gaimard, a species described from the Rio Macacu, a coastal river tributary of Guanabara bay, Rio de Janeiro. That synonymy was only formally proposed by Eigenmann (1910), and followed by most subsequent authors (e. g. Nielsen, 1974; Vari, 1992), except for Fowler (1975), who erroneously listed C. albula as the senior synonym of C. gilbert. Vari (1989) posteriorly removed both nominal species from Curimatus Oken (= Curimata Bosch) reallocating them in Cyphocharax Fowler, based on the lack of synapomorphic conditions present in other valid curimatid genera. Vari (1989) considered that those nominal species belonged to a major group within Cyphocharax also including C. grandocule Fernández-Yépez, C. modestus Fernández-Yépez, C. santacatarinae Fernández-Yépez, and C. voga Hensel, based on the presence of a rhomboidal caudal pigmentation and “random body spotting”. Later, Vari (1992) included C. grandocule along with C. albula in the synonymy of C. gilbert, and listed several characters allowing further distinction of that species from the remaining species of the group (i.e., number of vertebrae, scales in transverse series, and pigmentation characters). Among the characters involving the pigmentation pattern, Vari (1992) stressed the lack of randomly arranged dark spots on the lateral and dorsolateral surfaces of the body in C. gilbert (versus present in C. voga).